PELAKSANAAN MANAJEMEN PENDIDIK DAN TENAGA KEPENDIDIKAN DALAM MENINGKATKAN PROFESIONALISME GURU DI SDN MEKAR MUKTI 01 CIKARANG UTARA BEKASI - Aulia, Nurul Affika; Amirudin, Amirudin; Muzaki, Iqbal Amar (Idaarah: Jurnal Manajemen Pendidikan, 2022)
The implementation of educator management in order to improve the professionalism of teachers at SDN Mekar Mukti 01 is very important to do. The purpose of this study is to find out how educator management improves teacher professionalism, and find out what factors support and hinder the improvement of teacher professionalism through the management of educators and education personnel. It belongs to the qualitative type of descriptive research by photographing educational management patterns at the research locus. Data collection was carried out by triangulation, namely observations, interviews, field notes, and documentation of each aspect that was used as research material. The results showed that SDN Mekar Mukti 01 has gone through a less effective management cycle with the management of education in the school concerned.